2020
DOI: 10.1177/0896860820918135
|View full text |Cite
|
Sign up to set email alerts
|

eHealth interventions to support patients in delivering and managing peritoneal dialysis at home: A systematic review

Abstract: Peritoneal dialysis (PD) requires patients to develop a variety of self-management skills in order to effectively deliver and manage their dialysis at home. eHealth interventions may provide patients with accessible information to develop the skills and knowledge they require to manage their treatment. This review aims to identify and evaluate ‘active’ eHealth interventions in supporting patients on PD. Six databases were included within the review using the terms Peritoneal Dialysis, eHealth, telemedicine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 41 publications
4
35
0
1
Order By: Relevance
“…A similar review on e-health interventions in PD care was recently published by others [14]. That review included 15 studies, published between 1992 and 2018, representing 1343 patients receiving PD.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A similar review on e-health interventions in PD care was recently published by others [14]. That review included 15 studies, published between 1992 and 2018, representing 1343 patients receiving PD.…”
Section: Discussionmentioning
confidence: 93%
“…Despite the growing interest in the use of e-healthbased interventions in home-dialysis, both the reported interventions and studied outcomes are heterogeneous, thereby limiting evidence regarding effectiveness in terms of improvement of standardized clinical outcomes and associated impact on healthcare efficiency and economics [14]. Recently, the number of e-health initiatives and publications amplified, largely accelerated by the COVID-19 pandemic, resulting in seven new studies on this topic, representing 9377 patients receiving PD [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“… 19 Some studies reported the benefits of eHealth interventions in supporting patients on PD. 20 , 21 Considering the risks of traffic control, outpatient restrictions, and nosocomial infection during the outbreak, we encourage patients to stay at home rather than go to the hospital. We launched a follow-up and training plan through telehealth to improve the medical safety of patients during the pandemic period.…”
Section: Telehealth Applicationmentioning
confidence: 99%
“…Despite eHealth interventions to support PD patients in the delivery and management of home care, evidence of effectiveness is limited [ 25 , 26 ]. In particular, unlike other chronic diseases, PD home visits cannot be fully evaluated by outcome indicators.…”
Section: Introductionmentioning
confidence: 99%